Implants with hydrophilic surfaces equalize the osseointegration of implants in normo- and hyperglycaemic rats - Pinotti,Felipe Eduardo (2022)
Abstract The purpose of this study was to evaluate the effect of a surface modified by blasting and acid attack and maintained in an isotonic solution compared to a machined surface on osseointegration in normo- and hyperglycaemic animals. Sixty-four animals were allocated into 4 groups with 16 animals each, and they were subdivided into two experimental periods (15 and 45 days), with 8 animals in each group. The groups were divided according to the type of implant that was installed in the animals' tibia and the animals’ systemic condition: CM - Machined implants placed in Healthy animals; CH - Hydrophilic implants placed in Healthy animals, HM - Machined implants placed in animals with hyperglycaemia; HH- Hydrophilic implants installed in animals with hyperglycaemia. The following analyses were performed: biomechanical (removal torque), microtomographic (evaluation of the bone volume around the implants- BV/TV), and histomorphometric (evaluation of bone-implant contact BIC% and of the bone formation area between the threads BBT%). It was found that the implants with hydrophilic surfaces presented higher removal torques and quantities of BV/TV% and higher BIC% and BBT% values in normo- and hyperglycaemic animals. The results of this study indicated that the hydrophilic surface accelerates the osseointegration process (~ 15% BIC/BBT at 15-day period), especially in animals with hyperglycaemia. The hydrophilic surface equaled the osseointegration between normo- and hyperglycaemic animals, reversing the negative potential of hyperglycaemia on the osseointegration process.